2021
DOI: 10.1016/j.bja.2021.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after surgery with SARS-CoV-2 infection in England: a population-wide epidemiological study

Abstract: Background: The COVID-19 pandemic has heavily impacted elective and emergency surgery around the world. We aimed to confirm the incidence of perioperative severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and associated mortality after surgery. Methods: Analysis of routine electronic health record data from NHS hospitals in England. We extracted data from Hospital Episode Statistics in England describing adult patients undergoing surgery between January 1, 2020 and February 28, 2021. The e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…However at this time, due to missing studies, no recommendations could be made for the optimal time period between SARS-CoV-2 infection and elective surgery. Up to date, there are many publications, analyzing the perioperative mortality of patients with perioperative SARS-CoV-2 infection [ 100 ] and giving an evidence-based statement on postponing elective surgical interventions [ 101 ]. Table 1 summarizes some selected publications from the onset of the pandemic to the appearance of studies that examine the time interval in more detail [ 8 , 102 – 110 ].…”
Section: Increased Postoperative Mortality In Cases Of Perioperative ...mentioning
confidence: 99%
“…However at this time, due to missing studies, no recommendations could be made for the optimal time period between SARS-CoV-2 infection and elective surgery. Up to date, there are many publications, analyzing the perioperative mortality of patients with perioperative SARS-CoV-2 infection [ 100 ] and giving an evidence-based statement on postponing elective surgical interventions [ 101 ]. Table 1 summarizes some selected publications from the onset of the pandemic to the appearance of studies that examine the time interval in more detail [ 8 , 102 – 110 ].…”
Section: Increased Postoperative Mortality In Cases Of Perioperative ...mentioning
confidence: 99%
“…Pre‐operative SARS‐CoV‐2 infection was previously shown to be associated with significantly increased risks of morbidity and mortality. Data in the early phases of the pandemic demonstrated that peri‐operative SARS‐CoV‐2 infection was associated with clinically important increases in mortality, in some cases more than a 10‐fold increase [ 1 , 2 ]. Furthermore, when surgery was undertaken within 6 weeks of infection, postoperative morbidity and mortality were also increased [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative SARS-Cov-2 infection was previously known to be associated with a significant increased risk of morbidity and mortality. Data from the early phase of the pandemic showed that a perioperative infection from SARS-Cov-2 was clinically associated with an important increase in mortality, in some cases, as much as 10 times [ 6 , 7 ]. Furthermore, when surgery was undertaken within 6 weeks of infection, both postoperative morbidity and mortality increased [ 8 ].…”
Section: Resultsmentioning
confidence: 99%